2021
DOI: 10.3389/fimmu.2021.691715
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Classification and RBD Binding Properties of Neutralizing Antibodies Against SARS-CoV-2 Variants of Concern

Abstract: Severe acute respiratory syndrome coronavirus-2 (SAR-CoV-2) causes coronavirus disease 2019 (COVID19) that is responsible for short and long-term disease, as well as death, in susceptible hosts. The receptor binding domain (RBD) of the SARS-CoV-2 Spike (S) protein binds to cell surface angiotensin converting enzyme type-II (ACE2) to initiate viral attachment and ultimately viral pathogenesis. The SARS-CoV-2 S RBD is a major target of neutralizing antibodies (NAbs) that block RBD - ACE2 interactions. In this re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 46 publications
8
73
0
Order By: Relevance
“…C3 neutralising antibodies bound mainly to the outside of the ACE-2 binding site in both conformations. The C4 neutralising antibodies bound to an epitope farther from the ACE-2 binding site, which is only accessible following major conformational change in this area [23]. These findings are in alignment with those of Barnes et al who also reported 4 main classes of neutralising antibodies [24].…”
Section: Adaptive Immune Response: Protection Vs Severe Diseasesupporting
confidence: 85%
“…C3 neutralising antibodies bound mainly to the outside of the ACE-2 binding site in both conformations. The C4 neutralising antibodies bound to an epitope farther from the ACE-2 binding site, which is only accessible following major conformational change in this area [23]. These findings are in alignment with those of Barnes et al who also reported 4 main classes of neutralising antibodies [24].…”
Section: Adaptive Immune Response: Protection Vs Severe Diseasesupporting
confidence: 85%
“…Furthermore, it was shown that L452R confers viral escape from human leukocyte antigen (HLA)-restricted cellular immunity mediated by cytotoxic T lymphocytes ( 17 ). Finally, it was predicted that mutations in residue L452, which is located in immediate proximity to the RBD-ACE2 interaction interface, result in at least a modestly higher affinity of receptor binding and thus an increased rate of human cell infectivity ( 17 19 ). Both the successful immune escape and strengthened virus-cell attachment of L452 mutants might lead to increased transmissibility, infectivity, and/or pathogenicity of nCoV.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and characterization of nAbs targeting conserved RBD epitopes that possess dual advantage of breadth across Sarbecoviruses and higher resistance to neutralization escape is necessary to fight this pandemic (79). Due to the conservation at the Class IV epitope, antibodies targeting this site are of interest.…”
Section: Class 4 Antibodiesmentioning
confidence: 99%